Thermal management of Electronics: Numerical investigation of triangular finned heat sink. (1st May 2022) - Hithaish, Doddamani; Saravanan, V.; Umesh, C.K.; Seetharamu, K.N.
Highlights: Investigate flow and heat transfer characteristics of triangular pin fin heat sink for uniformly varying height, different orientation, and alternate arrangement of forward and backward triangular fins. The thermal performance index (TPI) with alternate forward and backward arrangement outperforms all other configurations of the range 1.01–1.44. The heat transfer coefficient (HTC) for 60° orientation is superior in the range of 3.36% to 11.32%. The HTC for Hf 0.75 fin height is 62.71%, higher than Hf 0.25 fin height. Abstract: The micro pin fin heat sink is an innovative method to enhance heat dissipation from the electronic system. The various geometrical configuration of the triangular micro pin fin heat sink (TMPFHS) for the fluid and heat transfer characteristics is numerically investigated in the present work. Finally, the best configuration is proposed. Three different configurations of triangular pin fin have been considered (i) uniformly varying the fin height ranging 0.25 mm-0.75 mm. (ii) Orientation of fin both in the clockwise and counter-clockwise direction (30°, 40°, 50 o, and 60°) (iii) Change in the direction of fins facing upstream fluid from forward triangular to backward triangular between two successive rows and vice versa. A 3-Dimensional numerical simulation is carried out for a triangular finned heat sink arranged staggered manner subjected to 10 W/cm 2 . A single-phase laminar flow is considered for Reynolds numbers ranging from 100 to 900 using coolant water. Results reveal that the heat dissipation rate for all the configurations increases substantially with the rise in pressure drop. A Non-dimensional parameter thermal performance index (TPI) is employed to access the superior heat sink in maximum dissipation and minimum pressure drop. The TPI with alternate forward and backward arrangement outperforms all other configurations of the range 1.01–1.44.